CODA : Processus de recherche-création — retour sur l’expérimentation de la médiation phénoménale d’un corps collectif performatif - Isabelle Choinière (Sillages Critiques)
The mediation of the performative body raises the question of the re-evaluation of the lived body related to certain phenomena of recreation, a recomposition involving the sensate and somatic body when it is affected by technology and incorporates the effects of technology. In order to understand this phenomenon, this essay suggests examining the interrelation of the notions of corporality (notion which concerns the physical body in its materiality, that is to say the anthropomorphic body), corporeality and embodiment in a transdisciplinary approach and as an anchoring to a dynamic of self-organization. With Merleau-Ponty’s philosophy underpinning the very foundations of this research, it will allow us to reflect on the new status of the contemporary body in the technological context. Two main notions will be used. “Corporeality”, as a form of the lived body and a transdisciplinary concept and embodiment as an act of integration by the body – here in a technological environment. In the evolution of the interrelation between the body and the changing environment, the two are in transrelation, a transformation occurs. To conclude, we propose to analyze these new “realities” in a Merleau-Pontian and Nietzschean interconnected approach, that is, through a philosophy “of becoming”, a philosophy that flows through the body: being a body, doing, risking and creating – a philosophy that resonates with this transformation.